Melt‐Processable and Electrospinnable Shape‐Memory Hydrogels - Turdimuhammad Abdullah; Cagatay Altınkok; Oguz Okay (Macromolecular Materials and Engineering)
Abstract Due to their ability to adapt to subtle changes in response to various external and internal stimuli, smart hydrogels have become increasingly popular in research and industry. However, many currently available hydrogels suffer from poor processability and inferior mechanical properties. For example, the preparation of a hydrogel network that can be subjected to melt processing and electrospinning is challenging. Herein, a series of mechanically strong, shape‐memory hydrogels based on polyacrylic acid (PAAc) chains containing 20–50 mol% of crystallizable n‐octadecylacrylate (C18A) segments are prepared by an organosolv method followed by in situ physical cross‐linking via hydrophobic interactions. The hydrogels exhibit a reversible strong to weak gel transition at 50–60 °C and can be melt‐processed at 60–100 °C, depending on the molar fraction of C18A. Additionally, the hydrogels can be dissolved in chloroform/ethanol mixture to form a viscous solution, which can then be used to produce a nanofibrous network by electrospinning. Effects of polymer concentration, volume ratio of solvents, and mole fraction of C18A on electrospinning are investigated to produce smooth, uniform nanofibers with small fiber diameter. The produced nanofibers, while maintaining their chemical structure, show significantly improved water adsorption capacity, enhanced mechanical properties, and fast shape‐memory performance.